Fetal outcome in women with borderline amniotic fluid index at pregnancy 36 weeks and beyond - Sweta; Mendiratta, Suman Lata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim of the study were to evaluate the fetal outcome associated with borderline amniotic fluid index (AFI) at pregnancy 36 weeks and beyond and to study the mode of delivery among these patients. Methods: A 60 pregnant subjects who were at 36-42 weeks period of gestation and ultrasonically diagnosed to have AFI less than or equal to 8 cm were included in the study and were compared to 50 pregnant patients with normal amniotic fluid. They were monitored throughout labour and fetal outcome was studied. Results: Fetal distress was observed in 60.4% cases leading to immediate termination of pregnancy. Incidence of meconium stained liquor was found significantly high (75%). Neonatal morbidity was found to be significantly high. Low birth weight (31.6%), Apgar score less than 7 at 5 minutes (20%), NICU admission (71.6%), meconium stained liquor (23.3%) were observed. Conclusions: That there is a high risk of adverse perinatal outcome in cases of Borderline AFI at pregnancy 36 weeks and beyond. Providing intensive intrapartum monitoring and good NICU facilities for such cases is necessary to optimise the fetal outcome.